Effect of Tunable Dielectric Core on Optical Bistability in Cylindrical Core–Shell Nanocomposites - Shewa Getachew (Advances in Condensed Matter Physics)
In this paper, the effect of a tunable dielectric core on local field enhancement, induced optical bistability, and the optical bistability domain in cylindrical core–shell nanoparticle composites are studied. The local field enhancement factor increases significantly at two resonant frequencies. The results demonstrate that the local field enhancement factor in the cylindrical core–shell nanoparticle increases when the natural attribute of the dielectric function of the dielectric core is varied by adding a dielectric function to it. Furthermore, we demonstrated that the magnitude of the imaginary part of the active dielectric core increases as the onset and offset input intensities increase. This indicates that the optical bistability or threshold width range widens as the imaginary part of the dielectric function of the dielectric core increases, thereby enlarging the threshold domain to improve system activation.